Autologous Adipose Stromal Cells Seeded onto a Human Collagen Matrix for Dermal Regeneration in Chronic Wounds. Issue 2 (August 2015) - Lafosse, Aurore; Desmet, Céline; Aouassar, Najima; André, Wivine; Hanet, Marie-Sophie; Beauloye, Christophe; Vanwijck, Romain; Poirel, Hélène A.; Gallez, Bernard; Dufrane, Denis
<x xml:space="preserve">Abstract</x> Background: Nonhealing wounds are unable to integrate skin autografts by avascular and fibrotic dermal tissue. Adipose-derived stromal cells can improve the local environment of the wound bed by angiogenesis and immunomodulation. This work aimed to develop a biological dressing made of adipose-derived stromal cells onto a human acellular collagen matrix. Methods: Adipose-derived stromal cells were isolated from human adipose tissue (n = 8). In vitro, the genetic stability during early and late passages (1, 4, 10, and 16) and vascular endothelial growth factor (VEGF) secretion were assessed. Adipose-derived stromal cell adhesion and spreading on collagen matrix were preliminarily studied. In vivo tumorigenicity, angiogenesis, and tissue oxygenation were assessed after implantation of the construct in nude rats (n = 10). The biological dressing was manufactured and implanted in three patients with chronic wounds. Results: In vitro, aneuploidies, but no clonal transformation, were detected up to late cellular passages. VEGF was secreted more during hypoxia (0.1% oxygen) than during normoxia (21% oxygen). Adipose-derived stromal cells can adhere and spread on the scaffold within 18 to 20 days. No tumor development occurred 3 months after implantation in immunocompromised rats. Vessel counts and tissue oxygenation were higher after adipose-derived stromal cell implantation. In patients, granulation tissue was found (276 percent of vessel density), followed by epithelialization or split-thickness skin engraftment up to 22 months after implantation. Conclusions: Implantation of adipose-derived stromal cells seeded onto human acellular collagen matrix (biological dressing) represents a promising therapy for nonhealing wounds, offering improvement in dermal angiogenesis and remodeling. This therapy using autologous stromal cells is safe, without significant genetic alterations after in vitro expansion.